Oxidation of tertiary benzamides by 5,10,15,20-tetraphenylporphyrinatoiron(III) chloride-tert-butylhydroperoxide - Constantino, L (2015)
Tertiary benzamides are oxidized by the 5,10,15,20-tetraphenylporphyrinatoiron(III) chloride-(BuOOH)-O-t system at the alpha-position of the N-alkyl groups. The major products are N-acylamides, although small amounts of secondary amides, the products of dealkylation, are also formed. Plots of initial rate versus initial substrate concentration for these reactions are curved, suggesting formation of an oxidant-substrate complex. The reaction rates are almost insensitive to the substituent in the benzamide moiety, but there is a kinetic deuterium isotope effect of 5.6 for the reaction of the N, N-(CH3)(2) and N, N-(CD3)(2) compounds. Comparison of the reaction products from N-alkyl-N-methylbenzamides reveals that, for all compounds studied except N-cyclopropyl-N-methylbenzamide, oxidation of the alkyl group is preferred, strongly so (by a factor of ca. 8) for N-allyl-N-methylbenzamide. In contrast to microsomal oxidation, there is no steric hindrance to oxidation of an isopropyl group. Thus, we propose that these reactions proceed via hydrogen atom abstraction to form an alpha-carbon-centred radical and we attribute the observed diminished reactivity of the N-cyclopropyl group to its known reluctance to form a cyclopropyl radical. Oxidation of N-methyl-N-(2,2,3,3-tetramethylcyclopropyl)methylbenzamide provides preliminary evidence for rearrangement of an intermediate radical. While it remains unclear how these reactions proceed directly to the N-acyl products, we have established that N- hydroxymethyl, N-alkoxymethyl and N-alkylperoxymethyl intermediates are not involved.